Ambulatory outpatient venous surgery service: An examination of patient satisfaction and experiences. (September 2022) - Hannon, Bernadette; Prizeman, Geraldine; Madhavan, Prakash; O'Neill, Sean; Martin, Zenia; O'Callaghan, Adrian; Colgan, Mary-Paula; Canning, Caitriona; O'Donnell, Sharon
Background: This study aimed to ascertain patients' experience of the out-patient venous service being provided, ; identify the level of patient satisfaction with the service and identify areas for further improvement and development. Method: A prospective descriptive quantitative study. A questionnaire was distributed to all patients who used the service between June 2017 and March 2018. A total of 195 questionnaires was distributed with 162 valid questionnaires returned; response rate of 83%. Results: This study found high satisfaction levels with endovenous ablation procedures, with concomitant phlebectomy, in the ambulatory outpatient setting and patient experiences of the service are overwhelmingly positive. Conclusion: Study findings support the management of ambulatory outpatient varicose vein endovenous ablation procedures as a feasible alternative to day surgery theatre settings and is the blueprint for future management of varicose vein surgery in Ireland.